2016
DOI: 10.1021/acs.jafc.6b00453
|View full text |Cite
|
Sign up to set email alerts
|

Improved Discrimination for Brassica Vegetables Treated with Agricultural Fertilizers Using a Combined Chemometric Approach

Abstract: Multielement and stable isotope (δ(13)C, δ(15)N, δ(2)H, δ(18)O, (207)Pb/(206)Pb, and (208)Pb/(206)Pb) analyses were combined to provide a new chemometric approach to improve the discrimination between organic and conventional Brassica vegetable production. Different combinations of organic and conventional fertilizer treatments were used to demonstrate this authentication approach using Brassica chinensis planted in experimental test pots. Stable isotope analyses (δ(15)N and δ(13)C) of B. chinensis using eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…Acetanilide (Puriss. p.a., Sigma-Aldrich) was used to calibrate elemental % C and % N. Multipoint calibration was applied using reference standard materials including B2155 (protein, δ 13 18 O/ 16 O value of the analytical samples and standards, respectively. The δ i E values are expressed in units "per mil" (‰).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetanilide (Puriss. p.a., Sigma-Aldrich) was used to calibrate elemental % C and % N. Multipoint calibration was applied using reference standard materials including B2155 (protein, δ 13 18 O/ 16 O value of the analytical samples and standards, respectively. The δ i E values are expressed in units "per mil" (‰).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In previous studies, δ 15 N isotopes have been reported to be a promising indicator for organic fertilization practice due to specific δ 15 N differences between synthetic fertilizers and unfermented animal manures, 11,12 compared to other available stable isotopes such as carbon (δ 13 C), hydrogen (δ 2 H), and oxygen (δ 18 O). Over the last 15 years, many studies have used δ 15 N analyses to discriminate organically and conventionally grown vegetables such as cabbage, 13 tomato, 14 sweet pepper, 15 lettuce, 4 brassica, 16 and a range of market vegetables. 17,18 Previous studies have also reported δ 15 N differences between organic and conventional rice.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, stable isotopic and multielemental signatures have played an increasingly important role in food forensics and the identification of production methods for plant-derived agroproducts (organic vs green or conventional) based on different fertilization practices. They have been successfully applied to various studies on vegetables, tea, cereals, and fruits. , In particular, the δ 15 N signature is deemed to be the most promising isotopic indicator for differentiating organically farmed crops from conventionally farmed counterparts . Organic farming systems rely on the use of organic fertilizers but exclude synthetic fertilizers produced by the Haber–Bosch process.…”
Section: Introductionmentioning
confidence: 99%
“…Las técnicas quimométricas, tales como el análisis de componentes principales (PCA) y el análisis discriminante lineal (LDA), son métodos estadísticos multivariados aplicados a: reducción de problemas dimensionales (número de variables), evitando así la pérdida de información esencial; reconocimiento de patrones; y caracterización de un conjunto de muestras Miller and Miller 2002). Aunque las técnicas de análisis quimiométrico multivarial se han aplicado a la clasificación de alimentos (Bilge et al 2015;Markiewicz-Keszycka et al 2018;Yuan et al 2016), actualmente no se informan estudios que implementen LIBS junto con técnicas quimiométricas para la caracterización de plaguicidas en vegetales.…”
Section: Pretratamiento De Espectrosunclassified